(untitled) (Cadernos de Sociomuseologia, 2022)
In this edition, we seek to present and analyze themes around social participation as the basis of museological work, through the analysis of different experiences in museological and cultural institutions, which transit between the concepts of museum, community museum and ecomuseum. The institutions presented are quite diverse, from ecomuseums and community museums in Brazil – Ecomuseum of Sepetiba, Living Museum of São Bento and Ecomuseum of Ilha Grande, in Rio de Janeiro, and Museum of Anthropology and Folklore Théo Brandão, in Alagoas . – until the resignification of the Los Cuchimilcos Museum, in Lima, Peru, and the National Museum of Fine Arts in Cuba. This diversity of institutions is an example of how wide the possibilities for action are around education and community participation in museology. Although the experiences gravitate around some shared assumptions, each of these ways of thinking and making museums has its specificities and peculiarities, the result of a way of acting that starts from the desires and needs of the communities that are inserted, in one way or another. . other and to varying degrees in these institutions. More than fundamental to seek a social function for each of the museums, and for museology itself, this participation becomes an important source of ideas and knowledge, which can subsidize and make it increasingly relevant for different populations. , the performances of the most diverse forms of museological and cultural institutions.